Pengaruh Penggunaan Media Pembelajaran Game Education Quizizz Terhadap Hasil Belajar Siswa pada Tema 8 Subtema 3 di Kelas VI SDN 2 Sumber Kidul - Rifki Ardiansyah; Fikriyah Fikriyah; Mimin Darmini (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research is motivated by the low interest of students in learning science, which in learning still uses conventional methods, resulting in student results not meeting KKM. Along with the times, several fields in life require to utilize technology, including in the field of education. For this reason, researchers conducted research by applying game-based learning media education in the learning process. The purpose of this study was to 1) determine student learning outcomes before using game education quizizz learning media 2) determine student learning outcomes after using game education quizizz learning media 3) determine the effect of using learning media and learning outcomes. This research was conducted using a quantitative approach involving one sample, so the research design that will be used by researchers is One-Group Pretest-Postest Desgin. Researchers will conduct tests before and after treatment in the classroom in order to compare with the situation before being treated. The population in this study is after all I-VI grade students of SDN 2 Sumber Kidul, totaling 230. The sample in this study were all VI grade students with 39 students. The results of the study state that from the results of hypothesis testing using the t test, it can be seen that the Sig value obtained is 0.000 smaller than 0.05, thus the results of the study entitled the effect of the use of game education quiz learning media on the learning outcomes of class students on theme 8 subtheme 3 in class VI SDN 2 Sumber Kidul there is a significant influence considering that all prerequisite analysis tests have shown results that are in accordance with the results of the data that has been processed by considering all hypotheses that include existing answers.